2017
DOI: 10.1074/jbc.m117.777748
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic induction of lipolysis in hepatocytes is inhibited by ethanol exposure

Abstract: In liver steatosis ( fatty liver), hepatocytes accumulate many large neutral lipid storage organelles known as lipid droplets (LDs). LDs are important in the maintenance of energy homeostasis, but the signaling mechanisms that stimulate LD metabolism in hepatocytes are poorly defined. In adipocytes, catecholamines target the β-adrenergic (β-AR)/cAMP pathway to activate cytosolic lipases and induce their recruitment to the LD surface. Therefore, the goal of this study was to determine whether hepatocytes, like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 70 publications
1
39
1
1
Order By: Relevance
“…Moreover, a PKA specific agonist increased CPT1A levels in primary hepatocytes [74]. In addition to fatty acid oxidation, inhibition of lipid droplet lipolysis via cytosolic lipases in alcohol-exposed hepatocytes has been recently demonstrated [75]. This inhibition was mediated by the inability of alcohol-exposed hepatocytes to activate PKA in response to β-adrenergic stimulation and recruitment of lipases to lipid droplets.…”
Section: The Role Of Camp In Nafldmentioning
confidence: 99%
“…Moreover, a PKA specific agonist increased CPT1A levels in primary hepatocytes [74]. In addition to fatty acid oxidation, inhibition of lipid droplet lipolysis via cytosolic lipases in alcohol-exposed hepatocytes has been recently demonstrated [75]. This inhibition was mediated by the inability of alcohol-exposed hepatocytes to activate PKA in response to β-adrenergic stimulation and recruitment of lipases to lipid droplets.…”
Section: The Role Of Camp In Nafldmentioning
confidence: 99%
“…These findings suggest that cytosolic lipases are also important regulators in LD turnover in hepatocytes (2). Interestingly, a more recent study reported that hepatocytes isolated from chronic ethanol-fed rats or acute ethanol-treated hepatoma cells that can metabolize ethanol showed significantly perturbed β-adrenergic stimuli-induced LD breakdown (3). Mechanistically, they found that ethanol inhibited PKA-mediated phosphorylation of HSL and the recruitment of ATGL to the LD surface resulting in the blockage of LD catabolism (3).…”
mentioning
confidence: 99%
“…Interestingly, a more recent study reported that hepatocytes isolated from chronic ethanol-fed rats or acute ethanol-treated hepatoma cells that can metabolize ethanol showed significantly perturbed β-adrenergic stimuli-induced LD breakdown (3). Mechanistically, they found that ethanol inhibited PKA-mediated phosphorylation of HSL and the recruitment of ATGL to the LD surface resulting in the blockage of LD catabolism (3). In addition to the above lipase-mediated LD breakdown, another emerging pathway to breakdown LD in hepatocytes involves the lipases and acidic hydrolases in lysosomes, a process known as “lipophagy”(4).…”
mentioning
confidence: 99%
“…Therapeutic targets to manipulate the lipid metabolism during NMP involve mainly the modulation of the production of enzymes involved with oxidation of FA for energy production and/or FA cellular exportation. As a consequence, cytoplasmic lipases play a key role as initiators in the mobilization of intracellular triacylglycerol stores and conversion into FAs and glycerol . Between those lipases, the adipose triglyceride lipase (ATGL) is considered to be the limiting rate factor for intracellular lipolysis in hepatocytes .…”
Section: Resultsmentioning
confidence: 99%